2015
DOI: 10.1016/j.compstruct.2015.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimisation of viscoelastic damping inserts in honeycomb sandwich structures

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Multi-objective optimisation of viscoelastic dampin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Boucher et al (2013) performed analytical, FE, and topological optimization studies to find the optimum locations of the inserts made of high damping material in the voids of the honeycomb cells (without increase in density). This study was extended further by Aumjaud et al (2015) for finding the optimum parameters of double-shear lap joint (DSLJ) inserts in a honeycomb sandwich panel using parametric optimization as well as adaptive indicator-based approaches. In these approaches, the damping was maximized while minimizing the extra masses of the inserts mounted on the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Boucher et al (2013) performed analytical, FE, and topological optimization studies to find the optimum locations of the inserts made of high damping material in the voids of the honeycomb cells (without increase in density). This study was extended further by Aumjaud et al (2015) for finding the optimum parameters of double-shear lap joint (DSLJ) inserts in a honeycomb sandwich panel using parametric optimization as well as adaptive indicator-based approaches. In these approaches, the damping was maximized while minimizing the extra masses of the inserts mounted on the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Rigid sandwich structures are widely used in military fields such as aerospace, shipping, and armored vehicles because of their high specific strength, specific rigidity, specific energy absorption, and other characteristics. With the continuous advancement of sandwich structure research, there has been much work carried out on the optimal design of the sandwich structure in order to meet the acoustics, thermal, and mechanical property requirements for different fields [ 1 , 2 , 3 , 4 ]. Namvar et al [ 5 ] used improved multi-objective particle swarm optimization with a genetic algorithm (MOPSOGA) to study the optimal design of a medium-thickness hexagonal honeycomb sandwich plate—highly accurate optimal velocity, inertia weight, and acceleration coefficient parameters were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Boucher et al [20] concluded that a partial occupation of the voids could be more efficient in terms of added weight. A parametric optimisation and the adaptive indicator-based evolutionary algorithm was employed by Aumjaud et al [22] in selecting damping insertion locations, focussing on the first two mode shapes.…”
Section: Introductionmentioning
confidence: 99%